Synthesis of polymer-stabilized metallic nanoparticles and their hydrogenation activity for vegetable oil - Wu, Lihua (2013)
Hydrogenation of vegetable oils is an important method to modify oils. However, high content of trans fatty acid (TFA) formed during hydrogenation disqualify the application of these hydrogenated oils in food industries. With the aims of producing hydrogenated oils containing low or zero TFA, polymer-stabilized metallic nanoparticles were designed and used as catalysts in this research. The objectives of this study include the preparations of polymer stabilized metallic nanoparticles, the characterization of the newly prepared nanoparticles and the hydrogenation of vegetable oils with the newly prepared nanoparticles as catalysts. The catalytic activity and selectivity were investigated and the reaction path ways are suggested. Chitosan (CTS) stabilized metallic nanoparticles were prepared with molar ratio of CTS to metal of 5:1. CTS-stabilized Pd nanoparticles were firstly investigated and the preparation conditions were optimized. Based on the optimum result, CTS-stabilized monometallic nanoparticles (CTS-Pd, CTS-Pt, CTS-Ru, CTS-Rh and CTS-Ir) were prepared at room temperature and atmosphere pressure, formic acid solution was used as both solvent and reducing agent. CTS-stabilized bimetallic nanoparticles were also prepared. CTS-Pd and CTS-Pt were selected as the first metals. The bimetallic nanoparticles were prepared by continual deposition of the second metals on the surface of the first metal. CTS demonstrated to be a good stabilizer for the preparation of nanoparticles in aqueous solution. The newly prepared nanoparticles can be stable in the colloidal solutions for more than half a year. Cyclodextrins (α, β and γ CDs) stabilized metallic nanoparticles were also prepared with molar ratio of CD to metal of 5:1. CD stabilized Pd nanoparticles (CD-Pd) can be prepared at room temperature and atmosphere pressure. 2-propanol was utilized as the optimum reducing agent. The nanoparticles can be stable for more than two weeks. However, CD-Pt cannot be prepared under the optimum condition. The structures of the newly prepared metallic nanoparticles were characterized. The UV-vis spectra showed that the metallic ions were reduced during the preparation. The newly prepared nanoparticles were mainly in spherical shape as shown from the TEM images. The average diameters of Pd based nanoparticles were larger than that of the relative Pt based nanoparticles. CTS-stabilized Pt based nanoparticles and γ-CD-Pd were obtained with small size (<10 nm) and narrow sizes distribution. Based on the XPS analysis, Pd and Pt in CTS stabilized Pd or Pt based nanoparticles were mainly in zero-valent while most of the secondary metals were in oxidized form. The interaction between CTS and the metals were also observed. Meanwhile, the interaction between CTS or CD and Pd were observed through the FT-IR results. The metallic nanoparticles were used as the catalysts for the hydrogenation of vegetable oils. The hydrogenation was conducted at room temperature and atmosphere pressure. 1-Propanol was used as a co-solvent to increase the solubility of oils. The results showed that the catalytic activity and selectivity for the hydrogenation was mainly influenced by the nature of the catalysts. Most of the CTS stabilized metallic nanoparticles and CD stabilized Pd show high activity while CD stabilized Pd achieve higher reaction rate. However, hydrogenation with CD-Pd based nanoparticles present higher selectivity for TFA under the same linoleate conversion. Thus, CTS stabilized Pd and Pt nanoparticles demonstrate as the optimum mono metallic nano catalysts. CTS stabilized Pt based nanoparticles produce lower TFA content under the same linoleate conversion. The additions of second metals show different influences to CTS-Pd and CTS-Pt. CTS-Pd-Ru, CTS-Pd-Zn, CTS-Pt-Fe and CTS-Pt-Ir are four bimetallic catalysts with both higher activity for C and lower selectivity for TFA. CTS-Pt-Fe demonstrates as the best catalyst which produced low TFA content (3.8%) at high conversion of C18:2 18:2 (92.3 %). Polyvinyl pyrrolidone (PVP) stabilized Pd and Pt monometallic nanoparticles (PVP-Pd, PVP-Pt) were prepared based on literatures and used for comparison study. Comparing with the PVP stabilized metallic nanoparticles, the newly designed nanoparticles in this research presented lower selectivity for TFA under the same conversion of C.Based on this research, the optimum CTS stabilized metallic nanoparticles were 18:2 obtained. The catalysts which have high activity for C and low isomerization of cis C 18:1 18:2 can be used to produce hydrogenated oils with high conversion of unsaturated double bonds and low content of TFA.